Dietary lysine and slaughter weight affect growth performance and carcass characteristics in boars and barrows - M M Rantanen; Robert H Hines; I H Kim; K G Friesen; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
During the growing and finishing period, the boars ate less, had better F/G, and were less fat than barrows. A high plane of nutrition (high vs moderate lysine concentrations for the growing-finishing phases) and decreasing slaughter weight from 260 to 220 lb also improved efficiency of gain and carcass leanness. However, many notable interactions occurred among the gender x lysine x slaughter weight treatments. Also, year (rotational-cross of average health status and lean growth potential vs a terminal-cross of high lean growth potential after repopulation of the farm) had pronounced effects on growth performance and carcass merits such that the combination of lean genotype-boars-high lysine-220 lb had advantages of 15, 20, 39,49, and 15% for ADG, ADFI, and F/G, avg backfat thickness, and fat-free lean index, respectively, compared to the control (i.e., the avg lean growth-barrows-moderate lysine-260 lb treatment).; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Barrows; Boars; Genotype; Slaughter weight